Modelling and optimization of bovine serum albumin adsorption on calcium bentonite using box-behnken experimental design method - Duranoglu, Dilek; Kumcu Yuen, Maya (IOP Publishing Ltd, 2024)
The purpose of this study is to investigate and optimize the process parameters for bovine serum albumin (BSA) adsorption onto calcium bentonite (CaB) using the Box-Behnken experimental design method. Calcium bentonite was characterized using FT-IR, SEM, XRD, zeta potential measurements, and Boehm titration methods. The BSA adsorption capacity of calcium bentonite was modelled with respect to pH (2.8, 4.8, and 6.8), temperature (25 degrees C, 32.5 degrees C, and 40 degrees C), and initial protein concentration (0.1-1.2 mg ml-1) using the Box-Behnken experimental design method. The Design Expert 13.0 software was used to optimize the process conditions and obtain three-dimensional response surface graphs. A regression model, which gives the relationship between the process parameters and BSA adsorption capacity, was obtained using Design Expert software. The developed model showed that the most effective parameter on adsorption was the initial protein concentration followed by pH and temperature. The maximum adsorption capacity was obtained about 171 mg/g under optimal conditions (pH 4.8, 40 degrees C, and 1 mg ml-1 of initial BSA concentration). BSA adsorption onto CaB fit the pseudo-second order kinetic model. This study showed that process parameters for BSA adsorption can be effectively investigated and optimized using the Box-Behnken experimental design method with a fewer number of experiments.
Keywords: calcium bentonite; bovine protein (BSA); box-behnken experimental design; modelling; optimization; PROTEIN ADSORPTION; CARBON; BSA; Physics